Cytogenetic Evolution and Research Trends in Coffea spp.: Integrating Bibliometric Analysis with Karyotype Evidence - Permatasari, Nindy; Fauziah, Lu’lu’ Kholidah; Sari, Resti Puspa Kartika; Hardani, Maisuri; ‘Aliyah, Siti Hamidatul; Siburian, Nora Vetty Vera; Saputra, Deni Tri; Nindita, Miftah Amalia; Rohidayanti, Iis; Aprilintan, Ayuhana; Syahputra, M. Damar; Kumalasari, Yuyun; Saputra, Rama Arsalta Bara; Alansyah, Rio Duta; Rahma, Chanda Rizkia; Simamora, Tomuan Harry Brossy; Rani, Zahra Fania Qud’; Priyambodo (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates cytogenetic evolution and research trends in Coffea spp. by integrating bibliometric analysis with karyotype-based evidence. Despite the rapid advancement of genomic research in Coffea spp., the integration of cytogenetic perspectives into broader research trends remains limited. Bibliometric data were retrieved from the Scopus database, covering publications from 1937 to 2026, resulting in 383 articles and reviews analyzed using Biblioshiny through thematic mapping and thematic evolution approaches. The results indicate that coffee genetic research has progressively shifted toward molecular and genomic studies, particularly those related to genetic variation, genome-wide association studies, and high-throughput analytical methods. In contrast, cytogenetic themes, including chromosome organization, karyotype variation, and polyploidization, remain comparatively underrepresented within the broader research landscape. Thematic evolution analysis further reveals a transition from foundational genetic studies to advanced genomic frameworks over time. Cytogenetic synthesis highlights major differences among key coffee species, with Coffea arabica characterized as an allotetraploid species (2n = 44), whereas C. canephora and C. liberica exhibit diploid chromosome complements (2n = 22). These findings demonstrate that chromosome-level perspectives remain insufficiently integrated into contemporary genomic research despite their importance in understanding genome evolution and species differentiation. By combining bibliometric trends with cytogenetic evidence, this study provides a more comprehensive framework for interpreting coffee genome organization and emphasizes the importance of integrating structural and molecular approaches in future coffee research and breeding programs.